2021
DOI: 10.1186/s12933-021-01270-1
|View full text |Cite
|
Sign up to set email alerts
|

Sacubitril/valsartan inhibits obesity-associated diastolic dysfunction through suppression of ventricular-vascular stiffness

Abstract: Objective Cardiac diastolic dysfunction (DD) and arterial stiffness are early manifestations of obesity-associated prediabetes, and both serve as risk factors for the development of heart failure with preserved ejection fraction (HFpEF). Since the incidence of DD and arterial stiffness are increasing worldwide due to exponential growth in obesity, an effective treatment is urgently needed to blunt their development and progression. Here we investigated whether the combination of an inhibitor of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 87 publications
0
6
0
1
Order By: Relevance
“…Sacubitril/Valsartan (LCZ696) is a new superstar in the management of heart failure and hypertension. Two recently-released independent studies showed that sacubitril/valsartan inhibits the progress of diastolic dysfunction and arterial stiffness to HFpEF in rat models ( 44 , 45 ). However, clinical trials are needed to verify the effects of sacubitril/valsartan on HFpEF patients.…”
Section: Does Treatment For Arterial Stiffness Benefit In Hfpef?mentioning
confidence: 99%
“…Sacubitril/Valsartan (LCZ696) is a new superstar in the management of heart failure and hypertension. Two recently-released independent studies showed that sacubitril/valsartan inhibits the progress of diastolic dysfunction and arterial stiffness to HFpEF in rat models ( 44 , 45 ). However, clinical trials are needed to verify the effects of sacubitril/valsartan on HFpEF patients.…”
Section: Does Treatment For Arterial Stiffness Benefit In Hfpef?mentioning
confidence: 99%
“…Избранная тактика ведения пациентки была нацелена в первую очередь на улучшение диастолической функции миокарда и, следовательно, предупреждение значимой объемной перегрузки ЛП и малого круга кровообращения при нагрузке и пароксизмах ФП, что сопровождалось развитием отека легких. В последние годы были проведены многочисленные исследования и опубликован ряд работ, свидетельствующих о способности как комбинации валсартана/сакубитрила [3,4], так и ингибиторов натрий-глюкозного котранспортера 2 типа [5,6] подавлять синтез провоспалительных цитокинов, угнетать окислительный стресс, восстанавливать эндотелиальную функцию, ионный и энергетический гомеостаз кардиомиоци-тов и фосфорилирование саркомерных белков, что нормализует механизм мышечного сокращения и приводит к уменьшению выраженности гипертрофии, интрамурального фиброза и ригидности миокарда с улучшением диастолической функции.…”
Section: Discussionunclassified
“…One of the early pathological abnormalities in DCM is diastolic dysfunction, which occurs when the heart is unable to relax and fill with blood properly [ 27 , 28 ]. This dysfunction is associated with diabetes-induced changes in cardiac lipid accumulation and calcium homeostasis, leading to ventricular stiffness and impaired relaxation.…”
Section: Cardiac Structural and Functional Anomalies In Dcmmentioning
confidence: 99%